REGULARITIES OF PROCESSES OF DEVELOPMENT OF PSYCHOPHYSIOLOGICAL FUNCTIONS OF STUDENTS DURING THE APPLICATION OF REMOTE AND AUDITORY LEARNING FORMATS - Serheta, I.V.; Vergeles, T.M.; Kizina, І.E.; Shkarivskyi, Yu.L.; Gunas, І.V. (World of Medicine and Biology, 2022)
In the course of the study the regularities of development of psychophysiological functions of the organism of student youth, which is in the conditions of using remote (on-line) and classroom (off-line) forms of organization of educational process in higher education institutions, are established. It was found that under the conditions of using the remote format of the educational process there was a marked improvement of indicators that noted such characteristics of the functional capabilities of the organism as the latent period of simple and differentiated visual-motor reactions (p
Keywords: students; psychophysiological functions; remote learning; classroom learning